Gritty Leaders: The Impact of Grit on Positive Leadership Capacity. Issue 4 (August 2019) - Schimschal, Sarah E.; Lomas, Tim
The concepts of grit and positive leadership are central to extraordinary performance. However, to date there has been little empirical analysis of the relationship between a leader's level of grit and their capacity to implement positive leadership strategies and practices. This correlational study explores these linkages, taking grit subfactors into consideration as well as three dimensions of positive leadership. Convenience sampling was used to survey 100 leaders across a range of industries. Respondents completed the Grit Scale and 18 questions from the Positive Leadership Practices Self-Assessment. Results indicated that grit positively correlated with positive leadership, and perseverance exhibited a stronger relationship than passion. Further, grit accounted for variance in positive leadership. These findings provide a solid evidence base for giving leaders access to development opportunities that can accelerate the growth of grit and positive leadership.